Adult blood stem cell localization reflects the abundance of reported bone marrow niche cell types and their combinations - Kokkaliaris, Konstantinos D.; Kunz, Leo; Cabezas Wallscheid, Nina; Christodoulou, Constantina; Renders, Simon; Camargo, Fernando; Trumpp, Andreas; Scadden, David T.; Schroeder, Timm (Blood, 2020)
The exact localization of hematopoietic stem cells (HSCs) in their native bone marrow (BM) microenvironment remains controversial, because multiple cell types have been reported to physically associate with HSCs. In this study, we comprehensively quantified HSC localization with up to 4 simultaneous (9 total) BM components in 152 full-bone sections from different bone types and 3 HSC reporter lines. We found adult femoral α-catulin-GFP+ or Mds1GFP/+Flt3Cre HSCs proximal to sinusoids, Cxcl12 stroma, megakaryocytes, and different combinations of those populations, but not proximal to bone, adipocyte, periarteriolar, or Schwann cells. Despite microanatomical differences in femurs and sterna, their adult α-catulin-GFP+ HSCs had similar distributions. Importantly, their microenvironmental localizations were not different from those of random dots, reflecting the relative abundance of imaged BM populations rather than active enrichment. Despite their functional heterogeneity, dormant label-retaining (LR) and non-LR hematopoietic stem and progenitor cells both had indistinguishable localization from α-catulin-GFP+ HSCs. In contrast, cycling juvenile BM HSCs preferentially located close to Cxcl12 stroma and farther from sinusoids/megakaryocytes. We expect our study to help resolve existing confusion regarding the exact localization of different HSC types, their physical association with described BM populations, and their tissue-wide combinations.